(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This article presents data on the state of the process of digitalization of the economy and concludes about the high level of development of information infrastructure, at the same time, there is a strong gap in the level of digitalization between regions. When assessing the impact of the development of Internet technologies on employment, two main consequences are identified: a decrease in the impact of the geographical factor on supply and demand in the labor market and the involvement of previously unoccupied social groups in the production process. The results of these consequences are divided into opportunities and threats for the population, and their analysis is carried out separately for the population of the periphery.